2011
DOI: 10.2967/jnumed.110.082404
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor Heterogeneity Characterized by Textural Features on Baseline 18F-FDG PET Images Predicts Response to Concomitant Radiochemotherapy in Esophageal Cancer

Abstract: 18 F-FDG PET is often used in clinical routine for diagnosis, staging, and response to therapy assessment or prediction. The standardized uptake value (SUV) in the primary or regional area is the most common quantitative measurement derived from PET images used for those purposes. The aim of this study was to propose and evaluate new parameters obtained by textural analysis of baseline PET scans for the prediction of therapy response in esophageal cancer. Methods: Forty-one patients with newly diagnosed esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
725
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(761 citation statements)
references
References 32 publications
32
725
1
3
Order By: Relevance
“…We investigated the reproducibility of several subtypes of GLCM entropy feature as they were reported as one the highest reproducible and predictive radiomic features 21, 27, 30. We included: Entropy, Summation Entropy, Difference Entropy in addition to first‐order Entropy (Intensity Histogram Entropy) .…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the reproducibility of several subtypes of GLCM entropy feature as they were reported as one the highest reproducible and predictive radiomic features 21, 27, 30. We included: Entropy, Summation Entropy, Difference Entropy in addition to first‐order Entropy (Intensity Histogram Entropy) .…”
Section: Discussionmentioning
confidence: 99%
“…In many previous F-18 FDG PET studies, the tumor characteristics were usually evaluated by the 3D-SUV max , which reflected only a single voxel with the maximum uptake, and few PET studies have focused on the intratumoral distribution of F-18 FDG [1,3,15]. The CSH method that we applied in our study was recently reported for parameterizing heterogeneous intratumoral F-18 FDG uptake in non-small cell lung cancer PET studies [3].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, evaluation of the intratumoral heterogeneity of F-18 FDG uptake may provide us with additional information about the tumor characteristics. A recent study reported that the detection of intratumoral metabolic heterogeneity on baseline F-18 FDG-PET is useful for predicting the response to concomitant radiochemotherapy in esophageal cancer [1]. However, no study has reported evaluation of the intratumoral distribution of F-18 FDG on PET to differentiate among tumors of unknown origin.…”
Section: Introductionmentioning
confidence: 99%
“…There are early reports that textural analysis, an additional tool quantifying intratumoural heterogeneity of 18 FDG-PET tracer uptake, may improve prediction of response and prognosis and it is hypothesised that image heterogeneity may be related to underlying biology and reflect the behaviour of malignant tumours [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%